1984
DOI: 10.1902/jop.1984.55.1.1
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Crevicular Leucocyte Response in Humans to a Chemotactic Challenge: Effects of Periodontal Diseases

Abstract: An in vivo assay was recently developed to monitor the crevicular leucocyte response to chemotactic agents, e.g., casein and N‐formyl peptides. This method was used to monitor humans with little or no gingival disease (C group), gingivitis (G group), chronic periodontitis (CP group) and localized juvenile periodontitis (LJP group). Casein (0.2 μ1, 2 mg/ml) was placed into an isolated gingival crevice of each subject with a calibrated wire loop and the time recorded (t = 0). Leucocytes were counted in crevicula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
0

Year Published

1986
1986
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…Resting cell counts in refractory patients were often as high or higher than the peak values. This is similar to the relationship reported by Singh et al (1984) for counts of LJP patients.…”
Section: N K Healthy Periodontium H = Refractory Patients -High Groupsupporting
confidence: 91%
See 1 more Smart Citation
“…Resting cell counts in refractory patients were often as high or higher than the peak values. This is similar to the relationship reported by Singh et al (1984) for counts of LJP patients.…”
Section: N K Healthy Periodontium H = Refractory Patients -High Groupsupporting
confidence: 91%
“…All of the refractory cases examined in this study exhibited a multiple-peak response to an in vivo chemotactic agent. In a recent study by Singh et al (1984) using the in vivo chemotaxis assay, patients with chronic periodontitis exhibited a single-peak response while patients with LJP exhibited a double-peak response. In the current study, the patients with refractory disease showed the multiple-peak response, not the single.…”
Section: N K Healthy Periodontium H = Refractory Patients -High Groupmentioning
confidence: 98%
“…In contrast, the UP patients showed an abnormal pattern with two peaks, one at 25 minutes and another at 45 minutes. The numbers of neutrophils migrating through the gingiva were lower than those in control subjects with comparable inflammation (Singh et al, 1984).…”
mentioning
confidence: 63%
“…Gillett and Wilton (1981) also reported that neutrophils accumulate in lesions of juvenile periodontitis patients, and quantitative studies by Singh et al (1984) show a marked reduction in the numbers of neutrophils migrating into the gingival crevice in UP patients. Sandholm (1984), in a light and scanning electron microscopic study of gingival washings, found migratory forms of neutrophils in samples taken from adult periodontitis patients.…”
mentioning
confidence: 97%
See 1 more Smart Citation